Institutional learning curve and factors of prolonged operation time of robotic distal pancreatectomy: An analysis of an initial 117 cases - Yuki Hirata; Laura Prakash; Jess Maxwell; Rebecca Snyder; Michael Kim; Hop Tran Cao; Ching‐Wei D. Tzeng; Jefferey E. Lee; Matthew H. G. Katz; Naruhiko Ikoma (Annals of Gastroenterological Surgery, 2025)
Abstract Background The granular methods by which centers can safely implement and effectively expand robotic distal pancreatectomy (RDP), including those related to appropriate patient selection during the learning curve period, remain unclear. This study aimed to verify that our strategic robotic surgical oncology program effectively implemented RDP as standard practice and to identify factors associated with prolonged operation time. Materials and Methods We performed a detailed analysis of the intraoperative and short‐term outcomes of consecutive patients (October 2018–September 2023) undergoing RDP at our center, beginning with the first patient in our program. Operation time was analyzed using a cumulative sum chart (CUSUM), and factors associated with prolonged operation time were analyzed. Results Throughout the study period, five surgeons performed RDP for 117 patients. The CUSUM analysis indicated our center required 18 cases to overcome the initial learning phase and 43 additional cases to become proficient. In contrast, when comparing short‐term outcomes across the three observation periods, there were no significant changes in the incidence of ACCORDION grade ≥3 pancreatic fistulas (p = 0.684), or readmission rates (p = 0.457). A multivariable analysis revealed BMI ≥30 in male, the presence of pancreatitis or fibrosis, and the performance of concomitant procedures were associated with extended operation times, while BMI ≥30 in female was not. Conclusions Although an institutional learning curve was observed, our program enabled the safe implementation of RDP and successfully expanded the number of primary operating surgeons while maintaining stable short‐term outcomes. The absence of an impact of high BMI on operation time in female patients suggests a notable advantage of robotic approach for these individuals.